Metropolitan Amfilohije’s Views on St Gregory Palamas and Orthodoxy: A Return to Palamism - Constantinos Athanasopoulos (Center for Hellenic Studies, 2021)
In what follows, I examine the views of Metropolitan Amfilohije’s views on St Gregory Palamas and Orthodoxy, primarily focusing on his PhD thesis, which was defended at the University of Athens, Faculty of Theology in 1973, and published in Thessaloniki in the same year. I claim that his views there not only show him defending Palamas, but also highlight the need for a strengthening of Palamism in Greece and abroad. Some of the problems, which he identified in 1973, exist in Orthodoxy today and his suggestion that all contemporary Orthodox intellectuals should persist in the Philosophy and Theology of Palamism seems to be the only way to solve these problems, even today.